Academic favoritism at work: insider bias in Turkish national journals - SARISOY, İDRİS (My University, 2022)
The study utilizes a unique dataset of 16,575 research papers published in 68 national Business and Economics journals to investigate editorial bias towards insiders in Turkish academia. The study questions insiders\" motive for their choice of journal and predicts faster acceptance for papers that contain insider authors relative to the outsider papers in anticipation of favorable editorial treatment. The findings show that insiders not only publish in large numbers in their affiliated institutions\" journals but also do so at significantly faster speeds. Specifically, 4938 (29.79% of) papers have at least one insider author, and they are accepted 41.5 days faster than the average outsider submission. Papers in English, junior professors, and new-generation university journals are less likely to have insider authors; while papers in Turkish, senior professors, old-generation university journals, and papers originating from graduate theses are more likely. Remarkably, national journals indexed in ESCI do not engage in editorial favoritism towards insiders and require considerably longer time to accept submissions. As Turkish universities are leading publishers of academic journals, the findings have important implications for the Turkish academia. We note a declining trend of insider authorship and provide suggestions to mitigate insider bias.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Kütüphanecilik; Bilgisayar Bilimleri; Bilgisayar Grafiği; Mühendislik ve Teknoloji; Social Sciences and Humanities; Sociology; Library Sciences; Computer Sciences; Computer Graphics; Engineering and Technology; BİLGİSAYAR BİLİMİ, İNTERDİSİPLİNER UYGULAMALAR; Bilgisayar Bilimi; Mühendislik, Bilişim ve Teknoloji (ENG); BİLGİ BİLİMİ VE KÜTÜPHANE BİLİMİ; Sosyal Bilimler Genel; Sosyal Bilimler (SOC); COMPUTER SCIENCE, INTERDISCIPLINARY APPLICATIONS; COMPUTER SCIENCE; Engineering, Computing & Technology (ENG); INFORMATION SCIENCE & LIBRARY SCIENCE; SOCIAL SCIENCES, GENERAL; Social Sciences (SOC); Information Systems and Management; General Social Sciences; Library and Information Sciences; Computers in Earth Sciences; Computer Graphics and Computer-Aided Design; General Computer Science; Computer Science (miscellaneous); Computer Science Applications; Social Sciences & Humanities; Physical Sciences; Editorial bias; Insider bias; Editorial favoritism; Turkish academia; Turkish journals; PUBLICATION BIAS; PRODUCTIVITY